2001
DOI: 10.1007/s00330-001-1146-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of swallowing using real-time TrueFISP MR fluoroscopy

Abstract: The aim of this study was to evaluate the ability of different real-time true fast imaging with steady precession (TrueFISP) sequences regarding their ability to depict the swallowing process and delineate oropharyngeal pathologies in patients with dysphagia. Real-time TrueFISP visualization of swallowing was performed in 8 volunteers and 6 patients with dysphagia using a 1.5 T scanner (Magnetom Sonata, Siemens, Erlangen Germany) equipped with high-performance gradients (amplitude 40 mT/m). Image quality of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 3 publications
2
42
0
3
Order By: Relevance
“…Anagnostara et al (5) reported that the turbo fast low-angle shot (Turbo-FLASH) sequence achieved 0.15-0.3 seconds/ slice using a 1.5T MRI system (Gyroscan ACS-NT; Philips Medical Systems, Best, The Netherlands). Barkhausen et al (10) reported that the true fast imaging with steady precession (TrueFISP) sequence produced 0.139 -0.405 seconds/image using a 1.5T MRI system (Magnetom Vision, Siemens, Erlangen, Germany). Ajaj et al (11) also used the real-time TrueFISP sequence and reported that it produced 0.5 seconds/ image using a 1.5T MRI system (Virtuosos; Siemens Medical Systems, Erlangen, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Anagnostara et al (5) reported that the turbo fast low-angle shot (Turbo-FLASH) sequence achieved 0.15-0.3 seconds/ slice using a 1.5T MRI system (Gyroscan ACS-NT; Philips Medical Systems, Best, The Netherlands). Barkhausen et al (10) reported that the true fast imaging with steady precession (TrueFISP) sequence produced 0.139 -0.405 seconds/image using a 1.5T MRI system (Magnetom Vision, Siemens, Erlangen, Germany). Ajaj et al (11) also used the real-time TrueFISP sequence and reported that it produced 0.5 seconds/ image using a 1.5T MRI system (Virtuosos; Siemens Medical Systems, Erlangen, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…The authors have found that swallowing requires a range of coordinated compressive and expansive movements that last in the order of 500 ms. From the obtained images, the strain rates experienced on the tongue have been estimated and found to be both positive and negative with a magnitude of about 0.2 per second. Developing fMRI techniques to study phenomena occurring during eating is an active area of research, but conclusive quantitative results have not been published yet (Barkhausen et al, 2002;Humbert and Robbins, 2007). A technique based on video rate endoscopy has also been developed and used to investigate the interactions between food material and oral surfaces, with an emphasis on food residues remaining in the mouth after swallowing; for example, the same study demonstrated that the material remaining onto the surfaces in the mouth after swallowing increased exponentially with increasing viscosity of the food (Watson et al, 2002;Adams et al, 2007;Pivk et al, 2008).…”
Section: Different Stages and Phenomena During Oral Processingmentioning
confidence: 99%
“…FIESTA is one of the high-speed MRI sequences that are combined under the name SSFP (steady-state free precession). The latter have been widely used to investigate the dynamic swallowing act [2,4,7,17]. Imaging with much higher time resolution is hence feasible, as is analysis in three spatial planes.…”
Section: Diskussionmentioning
confidence: 99%